Analisis Wacana Kritis Atas Nyanyian Bugis Seddi Juta Tellu Ratu Karya Ansar S. (Model Teun A Van Dijk) - Andi Filsah Muslimat (Institut Agama Islam Negeri Kendari, 2021)
The main objective of this research is to describe the structure, social cognition and social context contained in the Bugis song Seddi juta tellu ratu song from the work of Ansar S.Therefore, the description of the three dimensions of Van Dijk's model can make the community, especially Bugis singing lovers understand and enjoy the meaning contained and the linguistic aspects the creator wants to convey. The method used in this research is descriptive qualitative approach to critical discourse analysis. The results of this study indicate that there is a macro structure that includes a theme and a general description of injustice, a superstructure that includes an opening, a content and a closing so that it forms a complete frame structure, and a micro structure that includes semantics supported by background and metaphor. Dimensions of social cognition that are inspired by the social life of the text maker and the social context that influence it are the phenomena of promiscuity and uang panai.